Effect of high hydrostatic pressure challenge on biogenic amines, microbiota, and sensory profile in traditional poultry‐ and pork‐based semidried fermented sausage. Issue 4 (28th March 2020) - Borges, Ana F.; Cózar, Almudena; Patarata, Luís; Gama, Luis T.; Alfaia, Cristina M.; Fernandes, Maria J.; Fernandes, Maria H.; Pérez, Herminia Vergara; Fraqueza, Maria J.
Abstract : Abstract: The processing of traditional poultry‐ and pork‐based semidried fermented smoked sausages needs to be modernized to improve product quality and further extend its shelf life. The aim of the present study was to apply different combinations of high pressure (300 to 600 MPa) and time (154 to 1, 800 s) on the sausages using an experimental design based on response surface methodology. The chemical, microbial, and sensory characteristics of sausages treated with high‐pressure processing (HPP) were investigated. HPP application to semidried fermented sausages resulted in color changes, which could be dependent on the ingredients, formulation, and smoking conditions used. Nevertheless, none of the HPP treatments applied resulted in detectable changes in sensory properties, as tested in a triangle test and confirmed by the analysis of focus groups assessment. Significant differences were detected for lactic acid bacteria (LAB) counts from 344 MPa and 1, 530 s onward, with a marked decrease for the combination of 600 MPa and 960 s ( P < 0.05). Coagulase‐negative staphylococci showed higher tolerance to the increase in pressure than LAB. HPP induced a microbial reduction on Enterobacteriaceae, molds, and yeasts, minimizing the production of the main biogenic amines. However, the polyamines (spermine and spermidine) increased since their metabolic use by microorganisms did not occur. Given the reduction of the main spoilage microbial indicators with no detectable sensory changes observed with the binomial condition of 600 MPa and 960 s, this was chosen as the optimal combination to be further applied. Practical Application: The results from sensory analysis revealed that any of the HPP treatments applied resulted in detectable changes in sensory properties, as tested in a triangle test and confirmed by the analysis of the focus groups speeches.